Flood risk and housing prices: Evidence from Hungary - Gábor Békés; Áron Horváth; Zoltán Sápi (Hungarian Academy of Sciences, Institute of Economics, 2016)
This study employs the hedonic property price method to analyze the flood risk effect on a rich set of data. The analysis is carried out on Hungary, but as the control variables are extremely elaborated, our results have general importance. The paper finds a significant reduction in housing prices accounted to ZIP code level flood risk even after controlling for a wide range of geographical and socio-economic features. This paper finds that flood risk reduces housing prices substantially. It turns out that the average elasticity is driven by being in close proximity of major rivers. While riverside areas have an overall price premium in Hungary, risky areas loose this advantage to flood risk. In ZIP code areas where the inundation depths are 10% higher, housing prices tend to be 1% lower on average plus another 1% lower along the major rivers.
Keywords: Q51; Q54; R30; R31; 330; housing; hedonic pricing; flood risk; geography